The evolution of opsins and color vision: connecting genotype to a complex phenotype (2016)
Dissecting the genetic basis of adaptive traits is key to our understanding of evolutionary processes. A major and essential step in the study of evolutionary genetics is drawing link between genotype and phenotype, which depends on the difficult process of defining the phenotype at different levels, from functional to organismal. Visual pigments are a key component of the visual system and their evolution could also provide important clues on the evolution of visual sensory system in response to sexual and natural selection. As a system in which genotype can be linked to phenotype, I will use visual pigments and color vision, particularly in birds, as a case of a complex phenotype. I aim to emphasize the difficulties in drawing the genotype-phenotype relationship for complex phenotypes and to highlight the challenges of doing so for color vision. The use of vision-based receiver models to quantify animal colors and patterns is increasingly important in many fields of evolutionary research, spanning studies of mate choice, predation, camouflage and sensory ecology. Given these models impact on evolution and ecology, it is important to provide other researchers with the opportunity to better understand animal vision and the corresponding advantages and limitations of these models.